Corporate Governance Mechanisms, Information Transparency, and Firm Performance: A Study of Taiwan’s Listed Companies - Hung, Tzu-Han; Hung, Kuo-Chun; Lee, Meng-Che; Lee, Ming-Tsang; Chiang, Yi-Dun (International Journal of Business and Social Science Research, 2026)
The focus on corporate governance in Asian economies intensified following major U.S. accounting scandals and the 2008 financial crisis. These events sparked a demand for stricter regulations and prompted regional governments to adopt best practice principles to discipline corporate behavior. While theoretical foundations are solid, the empirical relationship between corporate governance and firm performance remains a subject of significant debate. In light of Taiwan’s increasing number of listed companies and the introduction of new governance frameworks, this research investigates the impact of corporate governance on the performance of public firms in Taiwan. The study finds that corporate governance significantly influences firm performance, though correlations across variables are not consistently positive. Furthermore, the analysis demonstrates that financial disclosure and transparency have a positive and significant effect on performance. These findings serve as a guide for investors and companies to assess critical governance elements and refine policy development.